Recording plasticity in neuronal activity in the rodent intrinsic cardiac nervous system using calcium imaging techniques - Smith, Joscelin E. G.; Ashton, Jesse L.; Argent, Liam P.; Cheyne, Juliette E.; Montgomery, Johanna M. (Frontiers in Synaptic Neuroscience, 2023)
The intrinsic cardiac nervous system (ICNS) is composed of interconnected clusters of neurons called ganglionated plexi (GP) which play a major role in controlling heart rate and rhythm. The function of these neurons is particularly important due to their involvement in cardiac arrhythmias such as atrial fibrillation (AF), and previous work has shown that plasticity in GP neural networks could underpin aberrant activity patterns that drive AF. As research in this field increases, developing new techniques to visualise the complex interactions and plasticity in this GP network is essential. In this study we have developed a calcium imaging method enabling the simultaneous recording of plasticity in neuronal activity from multiple neurons in intact atrial GP networks. Calcium imaging was performed with Cal-520 AM labelling in aged spontaneously hypertensive rats (SHRs), which display both spontaneous and induced AF, and age-matched Wistar Kyoto (WKY) controls to determine the relationship between chronic hypertension, arrhythmia and GP calcium dynamics. Our data show that SHR GPs have significantly larger calcium responses to cholinergic stimulation compared to WKY controls, as determined by both higher amplitude and longer duration calcium responses. Responses were significantly but not fully blocked by hexamethonium, indicating multiple cholinergic receptor subtypes are involved in the calcium response. Given that SHRs are susceptible to cardiac arrhythmias, our data provide evidence for a potential link between arrhythmia and plasticity in calcium dynamics that occur not only in cardiomyocytes but also in the GP neurons of the heart.